The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1259/bjr.20130147
|View full text |Cite
|
Sign up to set email alerts
|

Determination and comparison of radiotherapy dose responses for hepatocellular carcinoma and metastatic colorectal liver tumours

Abstract: Objective: The purpose of this study was to seek radiation dose responses separately for primary hepatocellular carcinoma (HCC) and metastatic (MET) colorectal liver tumours to establish tumour control probabilities (TCPs) for radiotherapy (RT) of liver tumours. Methods: The records of 36 HCC and 26 MET colorectal liver tumour patients were reviewed. The median dose per fraction and total dose were 4 Gy (2-10 Gy) and 52 Gy (29-83 Gy) for the HCC group and 3.6 Gy (2.0-13.0 Gy) and 55 Gy (30-80 Gy) for the MET g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 39 publications
1
35
1
Order By: Relevance
“…The dose-response associations derived from these studies are, however, not directly comparable to our findings. For one, radiosensitivity may be dependent on tumor type, similar to findings in external-beam radiotherapy (21). Furthermore, tumorabsorbed dose values are generally higher with glass microspheres, but this does not necessarily imply greater treatment efficacy.…”
Section: Discussionmentioning
confidence: 78%
“…The dose-response associations derived from these studies are, however, not directly comparable to our findings. For one, radiosensitivity may be dependent on tumor type, similar to findings in external-beam radiotherapy (21). Furthermore, tumorabsorbed dose values are generally higher with glass microspheres, but this does not necessarily imply greater treatment efficacy.…”
Section: Discussionmentioning
confidence: 78%
“…Areas less than one-third to one-half of the liver volume can tolerate more than 55 Gy. A study reported that liver lesions could be boosted to a total of 83 Gy (Lausch et al, 2013). We found that conventional fraction intense-modulated radiotherapy reduced liver damage and encouraged more normal cell regeneration than hyperfractioned radiotherapy, according to radiation biology (Dimri et al, 2013).…”
Section: Discussionmentioning
confidence: 85%
“…The required parameters D 50 and γ 50 , representing the dose needed for 50% tumor control and the slope of the response curve at that point, were obtained from the literature. The following [D 50 , γ 50 ] values were applied: breast [56.77, 1.48] (19), head-and-neck [59.3, 2.0] (20), liver [53.0, 1.2] (21), lung [74.5, 3.52] (22), and prostate [75.5, 2.25] (23). All treatment regimens employed have been translated to 2Gy/fraction schedules using the linear-quadratic model with α/β=10Gy for all sites except prostate, where a value of 2Gy was used (24).…”
Section: Methodsmentioning
confidence: 99%